Desperately Seeking Justice in Okky Madasari’s Bound (Jurnal Pembelajaran Sastra, 2021)
Resistance is often performed by marginal people as the response to the situation that is not benefitted them. Bound is a novel by Okky Madasari, which talks about marginal people’s resistance to injustice and their desperate struggle for humanity and decent life. The characters in this novel show the struggle for freedom and their resistance to the repressing power. The issue of resistance and the struggle against injustice is well explored for the readers to get the picture of what they feel and struggle for. This paper discusses the persistence of the characters’ resistance in the novel. This study aims to describe the resistance performed by some characters in the novel by applying the concept of resistance by James Scott (1985), elaborating the form of open resistance and closed resistance. This study indicates two forms of resistance in the novel, namely open resistance and closed resistance. Some characters in this novel, Cak Man, Sasana, and Jaka held an open resistance in the form of demonstration against the factory employer. Jaka, Sasana, and female workers are among the people who did resistance against the dominant group. The closed resistance is carried out by several characters in this novel, like Sasana's parents, who cried and cursed when Sasana was tortured by his friends and the perpetrators could not be brought into court because of their fathers’ position as the general and government officials.